Patterns of Gall Bladder Wall Thickening in Dengue Fever: A Mirror of the Severity of Disease - Parmar, Jitendra Premjibhai (Ultrasound Int Open, 2017)
BACKGROUND: Dengue fever is a major public health problem with an increased incidence in recent years. Gall bladder wall thickening has been reported as one of the most common findings in dengue fever. There is a paucity of literature regarding the various patterns of gall bladder wall thickening in dengue fever and their significance in predicting the severity of disease. METHODOLOGY AND SIGNIFICANT FINDINGS: Out of 93 seropositive patients included in the study, 54 patients with dengue fever had gall bladder wall thickening. 4 patterns of gall bladder wall thickening are demonstrated in this study. A uniform echogenic pattern in 20 patients, striated or tram track pattern in 11 patients, an asymmetric pattern in 2 patients and a honeycombing pattern in 21 patients. The range of patterns of wall thickening included normal wall thickening or uniform echogenic wall thickening in DF without warning signs, a striated or tram track pattern, and a honeycomb pattern in severe DF. Serial ultrasound done on consecutive alternate days revealed a change in the pattern of gall bladder wall thickening according to the severity of disease. CONCLUSION: The present study revealed 4 distinct patterns of gall bladder wall thickening. The uniform echogenic pattern was found to be more prevalent in dengue fever without warning signs, while the honeycomb pattern was found to be more prevalent in severe dengue fever. A change in the pattern of gall bladder wall thickening on subsequent serial ultrasound can predict the severity of the disease.